BIMBINGAN KEISLAMAN TERHADAP REMAJA DALAM MENGHADAPI PANDEMIK COVID 19 - Nurhasanah Nurhasanah; Eka Mei Ratnasari (INSTITUT AGAMA ISLAM NEGERI METRO, 2020)
Adolescents are one of the younger generations who are very vulnerable and need guidance from parents and families to be able to live their lives in a good way so that teenagers do not take the wrong path that can harm themselves and can even affect adolescent mentality.The ability of adolescents to adapt to the environment requires attention and direction from parents who can encourage adolescents to face every challenge they are facing, including to face the Covid 19 pandemic that has hit the whole world and even makes governments in each country limit physical contact with various regulations such as Work.From Home, School From Home and various other programs that will certainly have an impact on adolescent psychology.Islam as the Religion of Rahmatan lil alamin has certainly provided many teachings related to how to guide adolescents so that they are able to face every changing era properly and with full faith.